A brief history of fish osmoregulation: the central role of the Mt. Desert Island Biological Laboratory - Evans, David H. (Frontiers in Physiology, 2010)
The Mt. Desert Island Biological Laboratory has played a central role in the study of fish osmoregulation for the past 80 years. In particular, scientists at the MDIBL have made significant discoveries in the basic pattern of fish osmoregulation, the function of aglomerular kidneys and proximal tubular secretion, the roles of NaCl cotransporters in intestinal uptake and gill and rectal gland secretion, the role of the shark rectal gland in osmoregulation, the mechanisms of salt secretion by the teleost fish gill epithelium, and the evolution of the ionic uptake mechanisms in fish gills. This short review presents the history of these discoveries and their relationships to the study of epithelial transport in general.